Elettaria cardamomum (L.) Maton Essential Oil: An Interesting Source of Bioactive Specialized Metabolites as Inhibitors of Acetylcholinesterase and Butyrylcholinesterase - Marta Pavarino; Arianna Marengo; Cecilia Cagliero; Carlo Bicchi; Patrizia Rubiolo; Barbara Sgorbini (Plants, 2023)
Elettaria cardamomum (L.) Maton (Zingiberaceae family) is a plant traditionally used in Ayurvedic and Chinese medicine. In this work, the essential oil of E. cardamomum was found to inhibit the enzymes AChE (62.6% of inhibition, IC50 24.9 μg/mL) and BChE (55.8% of inhibition, IC50 25.9 μg/mL) by performing an in vitro colorimetric assay using the Ellman method. A bio-guided fractionation approach was used to isolate fractions/pure compounds that were tested individually to evaluate their activity. The resulting oxygenated fraction was found to be active against both AChE (percentage inhibition 42.8%) and BChE (percentage inhibition 63.7%), while the hydrocarbon fraction was inactive. The activity was attributed to a pool of oxygenated terpenes (α-terpinyl acetate, 1,8-cineole, linalool, linalyl acetate, and α-terpineol) that synergistically contributed to the overall activity of the essential oil.